Transgenic mice engineered to target Cre/LoxP-mediated DNA recombination into catecholaminergic neurons - Gelman, Diego Matias (2003)
To introduce restricted DNA recombination events into catecholaminergic neurons using the Cre/loxP technology, we generated transgenic mice carrying the Cre recombinase gene driven by a 9 kb rat tyrosine hydroxylase (TH) promoter. Immunohistochemistry performed on transgenic mouse brain sections revealed a high number of cells expressing Cre in areas where TH is normally expressed, including the olfactory bulb, hypothalamic and midbrain dopaminergic neurons, and the locus coeruleus. Double immunohistochemistry and immunofluorescence indicated that colocalization of TH and Cre is greater than 80%. Cre expression was also found in TH-positive amacrine neurons of the retina, chromaffin cells of the adrenal medulla, and sympathetic ganglia. We intercrossed TH-Cre mice with the floxed reporter strain Z/AP and observed efficient Cre-mediated recombination in all areas expressing TH, indicating that transgenic Cre is functional. Therefore, we have generated a valuable transgenic mouse strain to induce specific mutations of "floxed" genes in catecholaminergic neurons.